Assessment of the Tumorigenic Potential of Spontaneously Immortalized and hTERT-Immortalized Cultured Dental Pulp Stem Cells. (1st June 2015) - Wilson, Ryan; Urraca, Nora; Skobowiat, Cezary; Hope, Kevin A.; Miravalle, Leticia; Chamberlin, Reed; Donaldson, Martin; Seagroves, Tiffany N.; Reiter, Lawrence T.
Abstract : This study demonstrated that immortalized dental pulp stem cells (DPSCs) do not form tumors in animals and that immortalized DPSCs can be differentiated into neurons in culture. These results lend support to the use of primary and immortalized DPSCs for future therapeutic approaches to treatment of neurobiological diseases. Abstract: : Dental pulp stem cells (DPSCs) provide an exciting new avenue to study neurogenetic disorders. DPSCs are neural crest-derived cells with the ability to differentiate into numerous tissues including neurons. The therapeutic potential of stem cell-derived lines exposed to culturing ex vivo before reintroduction into patients could be limited if the cultured cells acquired tumorigenic potential. We tested whether DPSCs that spontaneously immortalized in culture acquired features of transformed cells. We analyzed immortalized DPSCs for anchorage-independent growth, genomic instability, and ability to differentiate into neurons. Finally, we tested both spontaneously immortalized and human telomerase reverse transcriptase ( hTERT )-immortalized DPSC lines for the ability to form tumors in immunocompromised animals. Although we observed increased colony-forming potential in soft agar for the spontaneously immortalized and hTERT -immortalized DPSC lines relative to low-passage DPSC, no tumors were detected from any of the DPSC lines tested. We noticed some genomic instability in hTERT -immortalized DPSCs but not in the spontaneously immortalized lines tested. We determined that immortalized DPSC lines generated in our laboratory, whether spontaneously or induced, have not acquired the potential to form tumors in mice. These data suggest cultured DPSC lines that can be differentiated into neurons may be safe for future in vivo therapy for neurobiological diseases. Significance: This study demonstrated that immortalized dental pulp stem cells (DPSCs) do not form tumors in animals and that immortalized DPSCs can be differentiated into neurons in culture. These results lend support to the use of primary and immortalized DPSCs for future therapeutic approaches to treatment of neurobiological diseases.